THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND MATERNAL ANXIETY LEVELS WITH FAILURE TO PROVIDE BASIC IMMUNIZATION AS SCHEDULED DURING THE COVID-19 PANDEMIC AT SIPATANA HEALTH CENTER - Irwan Irwan; Moh. Rivai Nakoe; Febrina Ganio (Journal Health & Science : Gorontalo Journal Health and Science Community, 2022)
Imunisasi yaitu suatu upaya untuk meningkatkan kekebalan seseorang secara aktif terhadap suatu penyakit, sehingga bila suatu saat terpajan dengan penyakit tersebut tidak akan sakit atau hanya mengalami sakit ringan. Berdasarkan data dari Dinas Kota Gorontalo menunjukkan bahwa imunisasi pada tahun 2019 ke tahun 2020, memiliki penurunan yang cukup dari pencapaian target 95% setiap tahun. Kebaruan penelitian ini karena meneliti tentang hubungan dukungan keluarga dan tingkat kecemasan ibu dengan kegagalan pemberian imunisasi dasar sesuai jadwal di masa pandemic Covid-19 di Puslesmas Sipatana. Tujuan penelitian untuk mengetahui hubungan keluarga dan tingkat kecemasan ibu dengan kegagalan pemberian imunisasi dasar sesuai jadwal di masa pandemic covid-19 di Puskesmas Sipatana. Metode penelitian ini adalah observasional analitik yaitu dengan pendekatan Cross Sectional.Populasi dan sampel pada penelitian ini adalah ibu yang memiliki bayi 0-12 bulan sebanyak 187 responden. Analisis data menggunakan ujistatistik Chi-Square. Hasil penelitian dalam variabel dukungan keluarga dengan kegagalan pemberian imunisasi yaitu nilai p-value 0,000 atau p ≤ 0,05. Dan  Tingkat Kecemasan Ibu dengan kegagalan pemberian imunisasi yaitu nilai P value 0,0002 atau P ≤ 0,05. Simpulan penelitian berdasarkan perhitungan menggunakan uji statistik Chi-Square bahwa ada hubungan antara dukungan keluarga dan tingkat kecemasan ibu dengan kegagalan pemberian imunisasi sesuai jadwal di masa pandemic Covid-19.Kata Kunci : Imunisasi; Dukungan Keluarga; Tingkat Kecemasan Ibu  AbstractImmunization is an effort to actively increase a person's immunity to a disease so that if one day exposed to the disease will not get sick or only experience mild pain. Data from the Gorontalo City Office shows that immunization from 2019 to 2020 has a sufficient decrease from achieving the target of 95% every year. The novelty of this study is that it examines the relationship between family support and maternal anxiety levels with the failure to provide basic immunizations as scheduled during the Covid-19 pandemic at Puslesmas Sipatana. The purpose of the study was to determine the family relationship and the level of maternal anxiety with the failure to provide primary immunization as scheduled during the COVID-19 pandemic at the Sipatana Health Center. Data analysis using Chi-Square statistical tests. This research method is analytical observational, namely with a Cross-Sectional approach. The population and sample in this study were mothers who had babies 0-12 months, with as many as 187 respondents. The study results in the family support variable with the failure to provide immunization were a p-value of 0.000 or p ≤ 0.05. And the level of maternal anxiety with the inability to provide immunization is a P value of 0.0002 or P ≤ 0.05. Based on calculations using the Chi-Square statistical test, the study concluded that there is a relationship between family support and maternal anxiety levels with the failure to provide immunizations as scheduled during the Covid-19 pandemic.Keywords: Immunization; Family Support,  Mother's Anxiety Levels